Assessment of Karst Groundwater Vulnerability to Contamination as a Tool for Delineation of Source Protection Zones: A Case Study in the Crimean Mountains - Tokarev Sergey Viktorovich; Amelichev Gennady; Braga Elena; Sereda Alexander (Russian Journal of Earth Sciences, 2024)
The assessment of groundwater vulnerability to contamination provides a hydrogeological basis for the designation of protection zones for drinking water sources. This paper presents a case study from the Crimean Mountains where karst groundwater plays a primary role in water supply. Groundwater vulnerability assessment has been carried out for two large karst springs: the Ayan and Krasnopeshcherny. For this purpose, a method adapted to the conditions of karst water formation in the region, called the Mountain-Crimean method, was used. The resulting source vulnerability maps of selected test sites demonstrate both similarities and differences. The common feature is the area predominance of the moderate vulnerability class, with a minor share of the low vulnerability class. However, the vulnerability classes on the two catchments have different placement patterns, as does the presence or absence of a high vulnerability class. The catchment area of the Krasnopeshcherny spring appeared to be more sensitive to pollution than the Ayan spring. The main reason is the hydrodynamic conditions of the deep parts of the karst aquifers drained by the springs. The karst aquifer of the Krasnopeshcherny spring has a much higher groundwater flow dynamic than that of the Ayan spring. The study closes by proposing a scheme of transition from vulnerability map to sanitary protection zones for karst water intakes in accordance with the regulatory standards of the Russian Federation.